2017
DOI: 10.1038/s41598-017-11830-9
|View full text |Cite|
|
Sign up to set email alerts
|

Secretory phospholipase A2-IIA overexpressing mice exhibit cyclic alopecia mediated through aberrant hair shaft differentiation and impaired wound healing response

Abstract: Secretory phospholipase A2 Group-IIA (sPLA2-IIA) is involved in lipid catabolism and growth promoting activity. sPLA2-IIA is deregulated in many pathological conditions including various cancers. Here, we have studied the role of sPLA2-IIA in the development of cyclic alopecia and wound healing response in relation to complete loss of hair follicle stem cells (HFSCs). Our data showed that overexpression of sPLA2-IIA in homozygous mice results in hyperproliferation and terminal epidermal differentiation followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…6 Bone morphogenetic proteins (BMPs) can inhibit hair follicle development. 7 The growth and development of hair follicles are also regulated by many signal pathways. The Wnt/⊎-catenin signal pathway plays an important role in the growth, development, and differentiation of hair follicles.…”
Section: Introductionmentioning
confidence: 99%
“…6 Bone morphogenetic proteins (BMPs) can inhibit hair follicle development. 7 The growth and development of hair follicles are also regulated by many signal pathways. The Wnt/⊎-catenin signal pathway plays an important role in the growth, development, and differentiation of hair follicles.…”
Section: Introductionmentioning
confidence: 99%
“…For cryosectioning, the skin samples were directly embedded in OCT compound (Tissue-Tek). The embedded skin was cryosectioned at 5 to 10-μm thickness on lysine coated slides and used for immunofluorescence staining as described earlier [2,21,22,37,38]. For the IHC of the tumour tissues, the antigen retrieval was performed by heating the slides in 10 mM sodium citrate (pH 6.0) in a microwave for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the skin, sPLA 2 -IIA is predominantly expressed in the proliferating keratinocytes of the basal layer of the epidermis [18,19]. Moreover, overexpression of sPLA 2 -IIA in transgenic mice led to epidermal hyperplasia and alopecia [[20], [21], [22]]. However, how the sPLA 2 -IIA affects the long-term maintenance of HFSC pool and its ultimate fate in the in vivo system is yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Using HF patch transplantation assay it has been demonstrated that HF stem cells contribute to generating new follicles in wounded mouse skin areas [72]. A complete reduction of HF stem cells in transgenic mice displayed a delay in wound healing after a full-thickness wound in the dorsal area [73]. Similarly, a delay in re-epithelization after the wound is observed in Edaraddcr/cr mice, that have a mutation in HF development [74].…”
Section: Major Functionsmentioning
confidence: 99%